Prophetic Leadership in Islamic Education Institutions Amid Digital Disruption and Global Educational Transformation Challenges - Yahya Mohammed Abu Bakr; Norakyairee Mohd Raus; Ahmed H. Ibrahim; Atta Ullah Faizi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to explore prophetic leadership in Islamic education institutions amid digital disruption and global educational transformation challenges. The rapid advancement of digital technologies, including artificial intelligence, has significantly reshaped educational governance, teaching practices, and institutional management. However, these changes also raise ethical, spiritual, and organizational challenges that require value-based leadership approaches. This research employs a qualitative library research design using a systematic literature review of scholarly sources. Data were analyzed using thematic content analysis to identify key themes related to prophetic leadership, digital transformation, ethical governance, and Islamic educational values. The findings reveal that digital disruption enhances institutional efficiency but also introduces risks such as ethical ambiguity, reduced human interaction, data misuse, and leadership fragmentation. The study identifies that prophetic leadership grounded in values such as ṣidq, amānah, ‘adl, and raḥmah provides a comprehensive ethical framework for addressing these challenges. The novelty of this study lies in the development of the Prophetic Digital Leadership Framework (PDLF), which integrates Islamic prophetic values with contemporary digital leadership theories. The study concludes that prophetic leadership is essential for ensuring that Islamic education institutions remain ethical, resilient, and human-centered in the digital age